Preventing Early Marriage through School–Community Partnerships in Islamic Education - Abdul Goffar; Wildan Miftahussurur (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Early marriage remains a persistent social and educational challenge in Indonesia, particularly in rural communities where cultural traditions, economic pressures, and religious interpretations intersect. Despite legal reforms aimed at raising the minimum marriage age, early marriage continues to affect adolescents’ educational continuity and well-being. This study aims to document and analyze a community-based educational intervention designed to address early marriage through school–community collaboration in an Islamic educational setting. The intervention was conducted in the form of an educational seminar at an Islamic secondary school, involving students, teachers, and school administrators. A qualitative descriptive approach was employed to capture participant engagement, institutional responses, and perceived outcomes of the program. Data were generated through observation, reflective discussion, and feedback from participants during and after the seminar. The results indicate increased awareness among students regarding the legal, health, and educational implications of early marriage, as well as strengthened institutional reflection among teachers and school leaders concerning their preventive roles. While no immediate behavioral change was observed, the intervention fostered dialogue, shared understanding, and initial commitment to collaborative prevention efforts. This study highlights the potential of school-based community engagement, particularly within Islamic educational institutions, as a culturally grounded entry point for early marriage prevention. Sustained collaboration and broader community involvement are necessary to translate awareness into long-term social change.